French post-modern masculinities : from neuromatrices to seropositivity - Schehr, Lawrence R. (Contemporary French and francophone cultures, 2009)
As traditional notions of masculinity have been put into question, there have been representational reactions to and articulations of changing masculinities in post-modern culture. Certain contemporary cultural productions in France are illustrative of these changing masculinities and this book offers an examination of these manifestations. It uses analysis of AIDS narratives, mainstream films, popular novels, more mainstream novels, a graphic novel, and rightist polemics to explore the changing meaning of masculinity in French society.